Variation of polysaccharides profiles in developing kernels of different barley cultivars. (January 2019) - De Arcangelis, Elisa; Messia, Maria Cristina; Marconi, Emanuele
Abstract: To evaluate the potential of immature barley grain as a source of bioactive compounds and to elucidate the correlations between polysaccharides accumulation during barley kernel maturation, samples of barley grains ( Hordeum vulgare L.) were collected at different stages after anthesis, including ripeness, and accumulation of fructan, β-glucan, total starch and proteins was studied. Fructan concentration in immature barley grain reaches a peak between 6 and 17 DAA with cultivar Scarlett accumulating the highest fructan content (9.5 g/100 g flour). β-Glucan and total starch showed a linear increase over ripening. Results obtained highlight physiological changes in polysaccharide accumulation during barley development and also supported the concept of immature barley kernel as an innovative functional ingredient contributing to fructan intake in the diet of the population. Highlights: Fructan and β-glucan content were investigated in developing barley kernels. Fructan concentration showed a peak between 6 and 17 days after anthesis. Cultivar Scarlett showed the highest fructan content (9.5 g/100 g flour). β-Glucan substantially accumulated from 20 days after anthesis onward. Immature barley flour can be potentially employed as a functional ingredient.